Use of mimosa (Mimosa pudica) leaf extract as an antibacterial for koi fish frys infected with Aeromonas hydrophila - Ismarica, Ismarica; Ningsih, Vella Gustia; Dewiyanti, Irma; Arisa, Iko Imelda; Nuzlia, Cut; Dewi, Cut Dara; Humeira, Humeira (Depik Jurnal Ilmu Ilmu Perairan, Pesisir, dan Perikanan, 2025)
This study evaluates the antibacterial potential of Mimosa pudica leaf extract for koi fry (Cyprinus carpio) infected with Aeromonas hydrophila. Specifically, it investigates the effects of immersion treatments at different concentrations, determines the optimal dose, and analyzes hematological responses. The research was conducted from December 2023 to January 2024 at the Fish Hatchery and Breeding Laboratory, Faculty of Marine and Fisheries, Syiah Kuala University. A Completely Randomized Design (CRD) was applied with six treatments A (negative control), B (positive control), C (Mimosa leaf extract 6%), D (Mimosa leaf extract 7%), E (Mimosa leaf extract 8%), and F (Mimosa leaf extract 9%) each with three replications. The results showed notable improvements in clinical symptoms of koi fry, including active swimming behavior, better feeding response, fading of red spots, reduced mucus production, normalized scales, absence of abdominal swelling, and restoration of normal eye color. ANOVA analysis of survival rate revealed a significant effect (P 0.05), with the highest survival observed in treatment F (86%) compared to treatment B (46%). In conclusion, Mimosa pudica leaf extract at a concentration of 9% (treatment F) provided the best results and can be recommended as a potential natural antibacterial for koi fry.Keywords:MimosaAeromonas hydrophilaKoi fishclinical symptoms